2015
DOI: 10.5772/61230
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Search, Bézier Curve-Based Lane Detection and Reconstruction System for an Intelligent Vehicle

Abstract: To improve the real-time performance and detection rate of a Lane Detection and Reconstruction (LDR) system, an extended-search-based lane detection method and a Bézier curve-based lane reconstruction algorithm are proposed in this paper. The extended-search-based lane detection method is designed to search boundary blocks from the initial position, in an upwards direction and along the lane, with small search areas including continuous search, discontinuous search and bending search in order to detect differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Huang et al [20] implemented a lane reconstruction system using a pair of Bezier curves. To improve reconstruction quality, they set a threshold and fitted the boundary with the Bezier curves.…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al [20] implemented a lane reconstruction system using a pair of Bezier curves. To improve reconstruction quality, they set a threshold and fitted the boundary with the Bezier curves.…”
Section: Dmentioning
confidence: 99%
“…The different types of road markings studied include straight [1], [5], [6], curved-lane [7]- [9], and multi-lanes roads [10]- [13]. Researchers have also studied lane boundary detection and tracking [14]- [16], road markings detection and classification [17], obstacle detection [12], [14], lane departure [18], [19], lane reconstruction [20], [21] and lane type classification [22]. However, previous studies rely on the assumption that the road networks remain static.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of splines are usable, e.g. : Bezier [39], B-splines [40], Catmull-Rom [41]. The spline can be divided into segments, and each segment is an degree polynomial.…”
Section: The Basic Of Bezier Splinesmentioning
confidence: 99%
“…The characteristic of this method is that it is highly robust to external interferences (such as utility poles and road signs) in lane line recognition. The models used to fit the lane line primarily include straight-line models, 46 segmented line models, 7,8 spline curve models, 914 and hyperbolic models. 15–17 Various studies 46 have indicated that the straight-line model is relatively easy to utilize, and its lane line fitting speed is faster than others.…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al 7 and Duong et al 8 adopted the segmented straight-line model to fit the curve lane line; their model can describe the direction of the front road but cannot accurately describe the bending degree of the lane. In the literature, 1013 the Bezier curve model, which is a spline curve model, was applied to fit curved lane lines. When the Bezier curve model is used to fit a lane line with a large curvature, some control points may be taken from areas outside the lane line, which is quite difficult.…”
Section: Introductionmentioning
confidence: 99%